Aromatic butenolides produced by a soil ascomycete Auxarthron sp. KCB15F070 derived from a volcanic island. Issue 45 (7th November 2019) - Kim, Jong Won; Son, Sangkeun; Kim, Gil Soo; Otaka, Junnosuke; Miura, Yuzuki; Muranaka, Atsuya; Uchiyama, Masanobu; Lee, Jung-Sook; Jang, Mina; Ko, Sung-Kyun; Takahashi, Shunji; Osada, Hiroyuki; et al.
Graphical abstract: Highlights: Three butenolide metabolites were isolated from Auxarthron sp. KCB15F070. Two butenolide glycosides possess a 2, 3-aryl substituted furanone backbone. The absolute configurations were determined by chemical and computational analysis. Abstract: LC/MS-based chemical screening of fungal extract fraction library led to identification of three 2, 3-aryl substituted furanone metabolites (1 –3 ), including one known butenolide glycoside (1 ) whose stereochemistry remained unsolved and two new compounds gotjawaside and gotjawalide (2 and3 ), from Auxarthron sp. KCB15F070, a fungus isolated from a soil sample of the volcanic island Jeju, Korea. Their planar structures were elucidated by 1D- and 2D-NMR spectroscopic and HRESIMS spectrometric techniques, and the absolute configurations of three compounds were solved using a combination of chemical derivatizations and computational analysis of vibrational circular dichroism (VCD) spectra.